Evaluation of a theater arts workshop to improve self-esteem and alleviate anxiety among gifted students in the arts - De Guzman, Ernestina M. (2009)
A theater arts workshop could be a way to be liberated from inhibitions and suppressed emotions. Games and exercises are designed to illustrate certain artistic and organizational concepts and principles. This study evaluated a theater arts workshop that aims to help gifted students in the arts cope with living in a special residential school. It used a pretest-posttest method with the instruments Self-Esteem Inventory for Filipinos and the Child Anxiety Scale. After the workshop, the level of self-esteem among the gifted students improved while their anxiety level decreased. This revealed that the Creative Drama module is most effective in helping students express express themselves and is effective in helping gifted students in the arts cope with living in a special residential school at the heart of the mountain.